Archaeometry and Archaeology: preliminary studies of the ceramics from archaeological sites of the upper Madeira river/Rondônia - Brazil. (Brazilian Journal of Radiation Sciences, 2021)
In southwest Amazonia, in the region of the Upper Madeira River, Rondônia, archaeological research has shown that communities with diverse cultures co-existed in the pre-colonial past (ca. 1,000 BP). Archaeological sites from this period located on river banks and islands consist of large extensions of ceramic deposits which reflect different daily activities and social positions that existed within these groups. The complexity of these societies is attested to by the diversity of both ceramic forms and iconography. In this work, 140 ceramic fragments from eight archaeological sites were studied by means of instrumental neutron activation analysis (INAA) to determine Na, K, La, Sm, Yb, Lu, U, Sc, Cr, Fe, Co, Zn, Rb, Cs, Ce, Eu, Hf, Ta and Th mass fractions, with the purpose of classifying and ordering artifacts which are related to one another in their chemical compositions. The analytical method used is adequate for this type of study because it is a semi-destructive technique with high sensitivity and precision that can determine chemical elements in trace and ultra-trace levels, essential for studying small variations in elemental concentrations. Multivariate statistical analyses were used to evaluate the dataset. Initially the mass fractions were normalized to compensate for the large difference in magnitude among elements determined in percentage and in trace level. Subsequently, the mass fraction data were interpreted through cluster analysis, discriminant analysis and a log-log scatterplot. The results show the existence of four compositional groups, indicating different clay sources.